Multiscale Thermal Management of Computing Systems - The MULTITHERMAN approach. Issue 1 (July 2017) - Bartolini, Andrea; Conficoni, Christian; Diversi, Roberto; Tilli, Andrea; Benini, Luca
Abstract: This work presents the research findings of the Multithermal ERC-Advanced project, in terms of multi-scale thermal control of complex large scale computing platforms such as High Performance Computing Systems, and datacenters. In this respect, the challenges and opportunities concerning thermal control of computing systems are discussed, along with the proposed innovative solutions. Control and management problem is divided at different hierarchical, and scale, levels (compute node and system). Then, given the control knobs and sensors available at each level, advanced control and system identification techniques are proposed, to achieve a holistic thermal management of complex computing platforms, with benefits for thermal stability guarantees and energy consumption optimization. Such features are of utmost importance for advancements in next generation large scale computing solutions.